Systematic Review: Relationship between Hospital Marketing Mix and Patient Visits and Hospital Selection - Lesmana Putra, Pandu; Gani, Ascobat (Journal of World Science, 2024)
This study aims to determine the relationship between hospital marketing mix, patient visits, and hospital selection. The study method uses the PRISMA method. Inclusion criteria were journals published from 2018 to 2022, focusing on marketing mix and hospitals. Journal searches were carried out using the keywords "Marketing Mix", "Hospital", and "Patient". Article searches were conducted in the Scopus, ScienceDirect, Proquest, Garuda, and Google Scholar databases. The research results found six articles that met the requirements to be included in the study for review. Four articles were conducted from the patient's perspective, and two were written from the perspective of hospital staff. The seven aspects of the marketing mix can influence patients to choose hospital services that implement marketing strategies. Elements of the marketing mix that have a relationship can differ from hospital to hospital. Hospitals need to plan a specific marketing strategy that focuses on patients so that patients want to choose to use the hospital's service facilities. The implications of this study are highly relevant for practitioners in the fields of hospital management and health marketing. The finding that the hospital marketing mix can influence patient choices provides a deeper understanding of the importance of appropriate marketing strategies in increasing patient visits and hospital competitiveness.